Grain filling improvement of rice by foliar fertilizer application under limited water supply - Isahak, Nur Fateha (2015)
Environmental stress factors such as limited water occur all over the world including in Malaysia. Generally, grain filling will reduce when limited water supply or drought was imposed during reproductive stages of rice cultivation throughout over the world. An experiment was conducted to select the best foliar fertilizer that can increase grain filling of rice under limited water supply. The variety of rice cultivated was MR219 by using pot. There were 36 totals of pots with three hills of paddy plant per pot. Six treatments were applied to the paddy; normal flooding, cyclic water stress for six days, cyclic water stress for six days + spermine, cyclic water stress for six days + silica, cyclic water stress for six days + brassinolide, and cyclic water stress for six days + multiple-compound fertilizer mixed with humic acid. Each treatment had six replications. Growth parameters were taken in range five to ten days after the treatment was applied. In yield attributes, the filled grain per hill, thousand grain weight, and etc was taken after harvesting. The experiment was conducted at Rice Research Centre, Greenhouse B at Ladang 10, UPM Serdang, Selangor. The treatments were laid out in a Randomize Complete Block Design (RCBD) and data obtained were analyzed using analysis of variance (ANOVA) with The Statistical Analysis System (SAS) software. The objective of this experiment was to find the best foliar fertilizer that can improve grain filling and yield of rice under limited water supply. All foliar fertilizer that has been applied to paddy plant showed positive impact on grain filling of paddy plant. The best foliar fertilizer that can be applied by farmers to overcome drought or water stress condition was spermine (2.06 ton haˉ¹).